Parametric study of the performance of a turbocharged compression ignition engine. (December 2014) - Menacer, Brahim; Bouchetara, Mostefa
In this study, the thermodynamic performance of a turbocharged compression ignition engine with heat transfer and friction term losses was analyzed. The purpose of this work was to provide a flexible thermodynamic model based on the filling-and-emptying approach for the performance prediction of a four-stroke turbocharged compression ignition engine. To validate the model, comparisons were made between results from a computer program developed using FORTRAN language and the commercial GT-Power software operating under different conditions. The comparisons showed that there was a good concurrence between the developed program and the commercial GT-Power software. We also studied the influence of several engine parameters on brake power and effective efficiency. The range of variation of the rotational speed of the diesel engine chosen extended from 800 to 2100 rpm. By analyzing these parameters with regard to two optimal points in the engine, one relative to maximum power and another to maximum efficiency, it was found that if the injection timing is advanced, so the maximum levels of pressure and temperature in the cylinder are high.